(untitled) (Eurasian Journal of Ecology, 2023)
The article provides data on the number of species of three families of the Zailiysky Kungei Alatau floristic area: Ranunculaceae, Paeoniacea and Berberidaceae recorded in two protected areas, Ile Alatau State National Nature Park (IA SNNP) and the State National Nature Park (SNNP) "Kolsai Koldery". In total, there were 82 species from 26 genera, or 97.6% of the flora of the Trans-Ili Kungei Alatau floristic region. Of those, 38 species from 17 genera were found in both protected areas. The largest genus, Ranunculus, had 26 species, of which 10 grew in both protected areas. Among these plants there were abundant, widespread, endemic, and rare species listed in the Red Book of Kazakhstan. There were two endemic and five rare species. Ranunculus dilatatus was an endemic of the Northern Tien Shan, and Anemone almaatensis was an endemic of Zailiysky Alatau. Both were found only in IA SNNP. Rare species listed in the Red Book of Kazakhstan were Hepatica falconeri, Gymnospermium altaicum, Adonis chrysocyathus, A. tianschanicus, and Berberis iliensis. Of those, only Adonis chrysocyathus and A. tianschanicus were found in both protected areas. The presence of Gymnospermium altaicum in the SNNP "Kolsai Koldery" requires verification. Most species of the families Ranunculaceae, Paeoniacea and Berberidaceae have different beneficial properties, including decorative and medicinal; some species are poisonous. Several species are weeds, the number of which increases sharply with grazing. One example is Aconitum leucostomum, which forms a special formation. In terms of life forms, grassy perennials predominate, and in terms of ecological and cenotic groups, meadow, forest-meadow and forest elements predominate. This is unsurprising given a boreal origin of the family Ranunculaceae. Key words: endemics, rare species, weeds, Zailiysky Alatau, Kungei Alatau.